Furniture form innovation and human–machine comfort evaluation model based on genetic algorithm - Yifan, Bai; Kamarudin, Khairul Manami; Alli, Hassan (World Scientific, 2024)
Mechanization, specialization, and shrewd steering have been regularly added to indoor fixtures commercial enterprises due to their ever-growing clinical and technological capacities. Competing in a marketplace in which technical layout competencies are required, the capability to think creatively and create novel shapes is what makes a product stand out and provides cost. Customers are no longer content material to buy fixtures in bulk, preferring as an alternative to choose pieces that are extra suitable to their own necessities and people in their homes, to higher fulfill primary demands and cope with problems like cramped quarters. The user’s needs for domestic product ergonomics inform the established order of a standards layer, which is then weighted to get its corresponding cost. In situations wherein competing gadgets provide similar features and overall performance, the aesthetics of the product grow to be more critical. This research explores the Pareto-primarily based Genetic Algorithm (PGA) inside this framework, with the goal of fostering innovation in product layout and the generation of novel ideas. Using more suitable K-means clustering and the Enhanced Least Squares Support Vector Machine (ELSSVM), this study gives a prediction technique for objectively assessing furniture comfort. Designers might be capable of focusing on aesthetics by using the findings as a springboard to research new shapes, way to the fact that the proposed version investigates several alternatives in pursuit of nice purposeful forms. Afterward, a mathematical version is used to symbolize the layout preference problems, and the layout scheme selection method is simulated. In the give-up, the advised model’s viability is checked by means of looking at how fixtures from the product’s layout picks had been carried out to assist designers give us fresh thoughts.